Applied Bayesian Analysis of Intergenerational Fingerprint Pattern Similarity - NK, Aswini; SHUKLA, RUDRANK; M C , Janaki (Politeknik Statistika STIS, 2025)
This research reports on the inheritance of fingerprint types across three generations of families. Uses of Bayesian measures of statistical analysis indicates a moderate transference of loops and whorls between generations (grandfather, father, son), with negligible transference for arches and only joint moderate evidence across all three generations. A total of 150 samples from 50 family trios were analyzed, classified fingerprints as Arch, Ulnar/Radial Loop, Composite, and Whorl. Cross-tabulation showed the highest transference in Ulnar/Radial Loops, followed by Whorls, with minimal transference for Arches and Composites. The Bayesian correlation analysis of father & grandfather and son & father showed strong similarities between generations (father & grandfather - Pearson r = 0.283, BF?? = 44.74; Kendall’s ?B = 0.255, BF?? = 4650.48) and substantial evidence for the association between sons and fathers. The analysis showed negligible transference between sons and grandfathers. Bayesian regression and model comparisons supported the null model, with very low R² values (0.003–0.012), indicating minimal predictive influence of parental patterns on the son’s fingerprint phenotype. Overall, the findings indicate moderate hereditary continuity of fingerprint patterns between successive generations, but weak evidence for transmission across all three generations. This suggests that fingerprint inheritance is complex, influenced by both genetic and developmental-environmental factors affecting dermatoglyphic patterns.